2012
DOI: 10.2139/ssrn.2079991
|View full text |Cite
|
Sign up to set email alerts
|

Social Science Studies and the Children of Lesbians and Gay Men: The Rational Basis Perspective

Abstract: This Article seeks to determine whether the social science literature on the children of lesbians and gay men precludes the government from relying on child welfare considerations to justify same-sex marriage bans and parenting restrictions affecting lesbians and gay men under the highly deferential rational basis test. Under that test, courts must uphold laws and regulations that have any conceivable basis of fact which is rationally related to a legitimate state interest. After comprehensively reviewing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…However, the most serious criticism was that the independent variable called "type of family," including allegedly same-sex families, was not measured consistently, thoroughly, or accurately. Others have made similar criticisms ( Gates, et al, 2012;Sherkat, 2012 ;Anderson, 2013 ;Ball, 2013 ;Becker & Todd, 2013 ;7 Sullins (2015d ), after restricting Wainright's sample to same-sex families and comparing unmarried and married same-sex couples, found that for some outcomes the children of married same-sex couples fared less well than children of unmarried same-sex couples or of heterosexual couples. Such an outcome raises the possibility that the duration of same-sex family life might play a role in outcomes for children rather than mere status of having been in a same-sex family for an unspecifi ed period of time or the marital status of the parents (which might be correlated with years duration of the parental relationship).…”
Section: Using Weak Independent Variablesmentioning
confidence: 91%
“…However, the most serious criticism was that the independent variable called "type of family," including allegedly same-sex families, was not measured consistently, thoroughly, or accurately. Others have made similar criticisms ( Gates, et al, 2012;Sherkat, 2012 ;Anderson, 2013 ;Ball, 2013 ;Becker & Todd, 2013 ;7 Sullins (2015d ), after restricting Wainright's sample to same-sex families and comparing unmarried and married same-sex couples, found that for some outcomes the children of married same-sex couples fared less well than children of unmarried same-sex couples or of heterosexual couples. Such an outcome raises the possibility that the duration of same-sex family life might play a role in outcomes for children rather than mere status of having been in a same-sex family for an unspecifi ed period of time or the marital status of the parents (which might be correlated with years duration of the parental relationship).…”
Section: Using Weak Independent Variablesmentioning
confidence: 91%
“…Most recently, Ball (2013), in a law review journal, in what he alleges is a comprehensive review of the social science literature claimed that…”
Section: Concluded Thatmentioning
confidence: 99%
“…Lansford (2009) has also highlighted the importance of multiple caregiver transitions for children’s outcomes. Ball (2013) acknowledged that “indeed, no one denies that, everything else being equal, children raised in intact two-parent households from a young age do better than children who experience family instability” (p. 727). For example, using national data from the United States, Fomby and Bosick (2013) found that parental instability was associated with “low rates of college completion, early union formation and childbearing, and an early entry into the labor force” (p. 1266), as well as other problem behaviors, including getting drunk, damaging school property, shoplifting, physically injuring someone else, truancy, lying, or staying out all night without parental permission (Fomby & Sennott, 2013).…”
Section: Part 1: Stability Of Same-sex Parent Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the discredited conviction that homosexuals are sexual predators who recruit children into the homosexual lifestyle still lives on in the Boy Scouts' policy prohibiting openly gay Scout Masters [44]. It also informs much of the anxiety over same-sex parenting that has surfaced in the context of the debate over marriage equality [45]. And, unfortunately, it still appears, from time to time, in family court decisions when children are involved [46].…”
Section: The Fourth Dimension Of Intersectionalitymentioning
confidence: 99%